ANALISIS TENTANG TINDAK PIDANA PENYELENDUPAN BAJU BEKAS IMPORT DI INDONESIA (Jurnal Hukum Mimbar Justitia, 2023)
The purpose of this study is to find out criminal sanctions for criminal acts of smuggling of export goods and imported goods in Indonesia. This research is normative juridical research. This research is descriptive. Data sources use primary legal material and secondary legal material. In Law No. 17 of 2006 concerning changes to the Republic of Indonesia Law No. 10 of 1995 concerning Customs (State Gazette of Indonesia No. 2006 Number 93 and Supplement to the State Gazette of the Republic of Indonesia Number 4661) criminal sanctions for smuggling as regulated in Article 102 have been regulated. , Article 102 A, and Article 102 B.  Keywords: Criminal Actions, Smuggling, Imported Used Clothes.